An economic evaluation of contingency management for completion of hepatitis B vaccination in those on treatment for opiate dependence. (6th May 2016) - Rafia, Rachid; Dodd, Peter J.; Brennan, Alan; Meier, Petra S.; Hope, Vivian D.; Ncube, Fortune; Byford, Sarah; Tie, Hiong; Metrebian, Nicola; Hellier, Jennifer; Weaver, Tim; Strang, John
Abstract: Aims: To determine whether the provision of contingency management using financial incentives to improve hepatitis B vaccine completion in people who inject drugs entering community treatment represents a cost‐effective use of health‐care resources. Design: A probabilistic cost‐effectiveness analysis was conducted, using a decision‐tree to estimate the short‐term clinical and health‐care cost impact of the vaccination strategies, followed by a Markov process to evaluate the long‐term clinical consequences and costs associated with hepatitis B infection. Settings and participants: Data on attendance to vaccination from a UK cluster randomized trial. Intervention: Two contingency management options were examined in the trial: fixed versus escalating schedule financial incentives. Measurement: Life‐time health‐care costs and quality‐adjusted life years discounted at 3.5% annually; incremental cost‐effectiveness ratios. Findings: The resulting estimate for the incremental life‐time health‐care cost of the contingency management strategy versus usual care was £21.86 [95% confidence interval (CI) = –£12.20 to 39.86] per person offered the incentive. For 1000 people offered the incentive, the incremental reduction in numbers of hepatitis B infections avoided over their lifetime was estimated at 19 (95% CI = 8–30). The probabilistic incremental cost per quality adjusted life‐year gained of the contingency management programme was estimated to be £6738 (95% CI = £6297–7172), with an 89% probability of being considered cost‐effective at a threshold of £20 000 per quality‐adjusted life years gained (97.60% at £30 000). Conclusions: Using financial incentives to increase hepatitis B vaccination completion in people who inject drugs could be a cost‐effective use of health‐care resources in the UK as long as the incidence remains above 1.2%.